A prospective study of myeloperoxidase levels in water immersion. (1st June 2022) - Ibanoglu, Mujde Can; Köse, Caner; Yilmaz-Ergani, Seval; Arslan, Burak; Akpınar, Funda; Engin-Ustun, Yaprak
Abstract: Introduction: We aimed to compare myeloperoxidase levels in cord blood samples of mothers undergoing water immersion or conventional labor. Method: We enrolled 52 pregnant women to this case control study meeting the following criteria: uneventful gestational follow-ups, no history of known chronic or pregnancy-associated diseases, cesarean section or uterine operation, BMI <29.9 kg/m 2, single vertex presentation, normal fetal heart rate pattern, 37–41 weeks of gestation, estimated fetal weight of 2500–4000 g. The subjects were either undergoing immersion in water (n = 26) or conventional labor (n = 26) and their myeloperoxidase levels were measured from cord blood samples. Results: The mean age of the study population was 24.55 ± 4.9 years. The mean BMI and weight gain during pregnancy were 26.8 ± 2.7 kg/m 2 and 11.6 ± 5.3 kg, respectively. The mean age of gestation at birth was 39.6 ± 1.1 weeks, with a mean birth weight of 3205.5 ± 433.2 g. The subjects in water immersion and conventional labor groups showed no difference in terms of age, gestational age, BMI, and birth weight. The mean myeloperoxidase level was significantly lower in the water immersion group (759.8 ± 391.5 U/L) compared to that in the conventional labor group (1832.2 ± 1011.9 U/L, p = 0.004). Discussion: Immersion in water during the first stage of labor seems to be associated with low myeloperoxidase levels, suggesting reduced oxidative stress in this delivery method. Highlights: Water immersion is associated with lower myeloperoxidase levels. Labor pain and inflammation can be reduced by immersion in water. MPO levels will be an objective indicator of pain reduction.